DAMPAK PEREDARAN PRODUK CAKRAM OPTIK ISI (CD DAN VCD) BAJAKAN DI KOTA SURABAYA - Duwi Aprianti; Marwanto - (Kertha Negara : Journal Ilmu Hukum, 2013)
The phenomena which often happen in a creation of an art is copyright piracy,particularly in a product of optic disc in media visual product. This situation, create a badimpact for the artist nor the producer, who suffera financial lost in Indonesian. Indonesiangovernment should concern of this situation, and must involve in to this piracy situation.